A study on the relation between the social issues and the mission of the Church in the context of the Philippines - Bernardino, Rambie B. ([Quezon City, Phils.] : St. Andrew's Theological Seminary, 2014)
Basically, we can easily say that there are existing serious issues of social problem in the Philippines. Issues such as poverty, human rights violations and corruption in particular which impedes the important aspirations of many Filipino people to live a decent kind of life. Poverty deprives the unprivileged of the basic necessities in life most especially food and shelter, violation of human rights prevents people in expressing their freedom and corruption takes away the opportunity of most people to live a comfortable life for the advantages of the few and greedy people who are mostly serving in or government. These social realities cannot really be denied because almost every day if we cannot witness them directly or personally, we can see and hear them from the media but what is very much frustrating is that though these issues are being exposed to public knowledge, still, it seems that these problems are continuously growing. Thus, sometimes we cannot escape but to ask what the government is doing?
In partial fulfillment of the requirement for the Degree of Master in Divinity
A thesis presented to the Faculty of St. Andrew's Theological Seminary